Simple and Reliable Factor V Genotyping by PNA-Mediated PCR Clamping - Behn, Moira; Schuermann, Marcus (Thrombosis and Haemostasis, 1998)
Resistance to activated protein C (APC resistance) is the most common cause of thrombophilia and linked to a single point mutation in the factor V gene (G>A transition at nucleotide 1691). In the past, several PCR based methods have been proposed to determine the allelostatus of individual patients from small amounts of blood DNA including PCR followed by restriction fragment length polymorphism detection (PCR-RFLP), PCR using sequence-specific primers (PCR-SSP) and oligonucleotide ligation assay (OLA). Here, we present a novel approach based on the method of peptide nucleic acid(PNA)-mediated PCR clamping which is extremely sensitive to base pair mismatches. If PNAs specific for the two allelic variants are applied separately in each case a clear discrimination between a heterozygous or homozygous normal or homozygous Factor V Leiden status is possible and no further confirmation step is required. In a prospective study, 60 patients with suspected venous thrombosis events were tested and compared to the conventional PCR-RFLP technique. The concordance between both methods was 100%. PNA-based factor V genotyping, therefore, should be considered for large scale screening of those patients considered to be at risk for deep venous thrombosis.